Estudo da criação de valor compartilhado em cooperativa de crédito - Lunkes, Fernando Daniel (2023)
The creation of shared value can be defined as practices and operational policies that increase the competitiveness of a given company and can at the same time improve the socioeconomic conditions in the communities where the company operates and operates, generating a positive social impact. In the sector of financial institutions, credit unions stand out for providing activities that align their business with serving users and sharing values for members. Therefore, the objective of this study is to analyze and measure how internal and external users evaluate the creation of shared value through actions carried out by the cooperative Sicredi Vanguarda in the last three years. This is a qualitative, quantitative and descriptive research, approached through a single case study. To measure the data, questionnaires were applied to three publics belonging to cooperativism, management group, individual and legal entity. The results showed that the analyzed company in question has managed to align the practice of creating shared value with its business strategies and that it is possible to promote the sustainability and longevity of the business while creating and sharing social and environmental value.